Citrus hystrix D.C Juice Inhibits The Growth of Staphylococcus aureus - Novina Kusumawardhani; Anny Thuraidah; Nurlailah Nurlailah (Baiman Bauntung Batuah Center, 2020)
Citrus hystrix D.C. is a citrus-type citrus tribal plant, one of the most favored and developed fruits by the people of South Kalimantan Indonesia. Citrus hystrix D.C. contains useful chemical compounds, one of which is flavonoids, which function as antibacterial and play a critical role in inhibiting bacterial growth. The purpose of this study was to determine the antibacterial activity of Citrus hystrix D.C. juice at 25%, 50%, 75%, and 100% concentration on the growth of Staphylococcus aureus. This research is experimental with Posttest Only Control Group Design. The material used was local Citrus hystrix D.C., fresh and clean green, obtained from the Astambul area, Banjar Regency, South Kalimantan Indonesia. The results showed that there was a zone of inhibition of Citrus hystrix D.C. juice on Staphylococcus aureus growth which began at 25%, 50%, 75% and 100% concentrations of 13.75mm, 17.25mm, 19.75mm, and 21.75mm, so it can conclude that the juice of Citrus hystrix D.C. influences the growth of Staphylococcus aureus which has the largest inhibitory zone at a concentration of 100%.